The development of an indicator model for administrative management of faculty of physical education Thailand national sport university the road to a sport learning organization in ASEAN - Chudam, Wongphat (Edelweiss Applied Science and Technology, 2024)
This research aimed to examine the congruence of an indicator model for administrative management of Faculty of Physical Education Thailand National Sports University, the road to a sports learning organization in ASEAN with the empirical data. The research was implemented in 3 phases. The phase 1 aimed to study an administrative management indicator of Faculty of Physical Education, Thailand National Sports University, the road to a sports learning organization in ASEAN. An in-depth interview was used with 5 key informants selected by a purposive selection method. The instruments used were an in-depth interview and analytic induction. The phase 2 aimed to make indicators of administrative management of Faculty of Physical Education, Thailand National Sports University, the road to a sports learning organization in ASEAN. Key informants included 17 experts selected by a purposive selection method. The instrument used was a rating scale questionnaire to conclude the findings and determine administrative management indicators for Faculty of Physical Education, Thailand National Sports University, the road to a sports learning organization in ASEAN for the benefits of harmony and accuracy. The phase 3 aimed to examine the congruence of administrative management indicators for Faculty of Physical Education, Thailand National Sports University, the road to a sports learning organization in ASEAN. The sample comprised instructors, students of Faculty of Education and stakeholders, 490 persons in total. The instruments used in this phase were a rating scale questionnaire and confirmatory factor analysis. The research results indicated that 1) there were 5 aspects of the competency-based learning management indicator for professional education teacher students as follow: 1. Factors of administrative management mechanism, 10 indicators, 2. Factors of instructor quality, 6 indicators, 3. Factors of learning management, 17 indicators, 4. Factors of student capability enhancement, 9 indicators, 5. Factors of athlete capability enhancement to excellence, 7 indicators, 49 indicators in total. All of them were consistent, 2) the factor measurement model was consistent with the empirical data. It was found that the model was well congruent with the empirical data, considered from the relative Chi-square that was 0.487(well consistent), GFI (Goodness of Fit Index) was 0.674 (well consistent), AGFI (Adjusted Goodness of Fit Index) was 0.482 (fairly consistent), and RMSEA was 0.05 (fairly consistent). Therefore, the null hypothesis stating that the research model was congruent with the empirical data.